Comparison of Self-Declared Mobile Use While Driving in Canada, the United States, and Europe: Results from the European Survey of Road Users' Safety Attitudes. Issue 37 (December 2018) - Woods-Fry, Heather; Vanlaar, Ward G. M.; Robertson, Robyn D.; Torfs, Katrien; Kim, Woon; Van den Berghe, Wouter; Meesmann, Uta
Existing literature on hand-held mobile use while driving includes little research about the differences in prevalence worldwide. The current research aims to increase the available knowledge by comparing rates of self-reported hand-held mobile use behaviors while driving from three different regions (Canada, the United States, and Europe). Self-declared mobile use (talking on a hand-held mobile, sending a text message or email), personal acceptability, and attitudes toward mobile use while driving were measured as part of the E-Survey of Road Users' Attitudes (ESRA 1) conducted in 25 countries during 2015–2016. Survey data was collected uniformly, allowing for full comparability among regions. The descriptive analysis compared rates of drivers' mobile use behaviors, opinions, and attitudes by region. Two multivariate models predicting self-declared talking on a hand-held phone while driving, and self-declared sending of a text message or email while driving were also estimated. Regional comparisons of the descriptive results demonstrate that both self-declared behaviors were the lowest in Canada. Multivariate models show that U.S. drivers' personal acceptability, attitudes, and support for zero-tolerance measures had a significant effect on their self-declared rates of hand-held mobile use while driving. Furthermore, when examining self-declared talking on a hand-held mobile device while driving across all regions, a common social phenomenon known as the bandwagon effect was found, as those who agreed that almost all car drivers occasionally talk on a hand-held mobile while driving were 2.41 times more likely to report doing so themselves. Implications and suggestions for further research are discussed.